The idea of justice in oedipus king. An intersection of cultures in the elaboration of a tragedy. - García Alvarez, César (Byzantion Nea Hellás, 2006)
The present investigation analyzes the tragedy Oedipus King from the point of view of justice. Firstly, it deals with the theme of destiny both in philosophical cosmology and in the theological Greek period, so as to deal, secondly, with the several hybris Oedipus suffers.